2003
DOI: 10.1037/0022-3514.84.1.5
|View full text |Cite
|
Sign up to set email alerts
|

How chronic self-views influence (and potentially mislead) estimates of performance.

Abstract: An important source of people's perceptions of their performance, and potential errors in those perceptions, are chronic views people hold regarding their abilities. In support of this observation, manipulating people's general views of their ability, or altering which view seemed most relevant to a task, changed performance estimates independently of any impact on actual performance. A final study extended this analysis to why women disproportionately avoid careers in science. Women performed equally to men o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
176
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 398 publications
(187 citation statements)
references
References 70 publications
8
176
0
3
Order By: Relevance
“…Further, Ehrlinger and Dunning (2003) attribute inconsistencies between Selfperception and actual performance as a symptom of what they call the top-down nature of performance estimates. This is a process whereby a person who begins with an inflated sense of Self-capability uses those levels of Self-beliefs when making projected evaluations of their future performance, since performance evaluations are 'formed by referring to a person's chronic view about his or her abilities in the specific domain in question ' (p. 378).…”
Section: Discussionmentioning
confidence: 99%
“…Further, Ehrlinger and Dunning (2003) attribute inconsistencies between Selfperception and actual performance as a symptom of what they call the top-down nature of performance estimates. This is a process whereby a person who begins with an inflated sense of Self-capability uses those levels of Self-beliefs when making projected evaluations of their future performance, since performance evaluations are 'formed by referring to a person's chronic view about his or her abilities in the specific domain in question ' (p. 378).…”
Section: Discussionmentioning
confidence: 99%
“…It should be studied whether performance postdictions, performance judgments after the tests, also involve anchoring and adjustment processes. Research has shown that performance postdictions are influenced by selfperceptions of ability as well (e.g., Dunning et al 2003;Ehrlinger and Dunning 2003;Schraw and Roedel 1994). Specifically, Ehrlinger and Dunning (2003: Study 1) showed that participants' self-perceptions of logical reasoning ability were significantly and positively correlated with their postdictions on a logical reasoning task after controlling for actual performance.…”
Section: Directions For Future Researchmentioning
confidence: 96%
“…Specifically, Ehrlinger and Dunning (2003: Study 1) showed that participants' self-perceptions of logical reasoning ability were significantly and positively correlated with their postdictions on a logical reasoning task after controlling for actual performance. In Study 3, Ehrlinger and Dunning (2003) manipulated participants' self-perceptions of knowledge of geography using techniques such as asking questions that gave participants favorable or unfavorable impressions of their own geographical knowledge. The manipulation of self-perceptions influenced postdictions, independent of actual performance.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…basis of their theories or beliefs-for example, beliefs about self-efficacy or about their own ability (Ehrlinger & Dunning, 2003) or expertise . Self-efficacy is at least moderately stable over a period of 1 week (Lane & Lane, 2001), and the ability of reading comprehension is at least moderately stable over 5 months, as well (Byrne, 1986).…”
mentioning
confidence: 99%